Letting People Go - Shlosberg, Matt (Business Expert Press, 2010)
Ebook from IG Library ; If you manage people, you are probably responsible for firing them. The central message of this book is that layoffs and firings have to be done right. Layoffs and firings do happen. It's just the way business is done. But many companies mishandle terminations, resulting in lawsuits, mass employee exodus, theft, loss of productivity, brand destruction, and many other sicknesses. This book addresses both layoffs and firings and describes how to perform them correctly. It also addresses the role leadership plays in terminations and teaches readers how to have tough conversations.